If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -13 = 89 Reorder the terms: -13 + 5x = 89 Solving -13 + 5x = 89 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + 5x = 89 + 13 Combine like terms: -13 + 13 = 0 0 + 5x = 89 + 13 5x = 89 + 13 Combine like terms: 89 + 13 = 102 5x = 102 Divide each side by '5'. x = 20.4 Simplifying x = 20.4
| 6a-3=3a-9 | | 5k-4k=13 | | 4(2x-4)-16(3x-1)=0 | | (x^3)^1/3=16^1/3 | | 4(2b+3)=b+2 | | f(-3)+f(5)=5x+3 | | 2x-8=5-x | | 4b-5b=9 | | (2l+12)+2w=96 | | 12t-11t=10 | | -x-y=12 | | (7-x)(1-x)+18=0 | | 3(4-2y)+2(1+6y)=12 | | 25=-3m | | x^4+18x^2=0 | | x^4-8x^3+24x^3-32x-240=0 | | 5y-10y=10 | | 3(2y-1)=x+4 | | 2-11m=5p+3.2 | | -2=-2-18 | | 4x+2y+300-3x-4y=320 | | -6x+8y=17 | | 2(4-3x)=6-(6+1) | | 4m=6m-29 | | 2-y+2=3y | | 20=5y-3x | | 2l+12+2w=96 | | 25-[4+8y-4(y+5)]=-4(5y-5)-[8(y-1)-16y+11] | | -4x+6y=20 | | 4(x+9)=6x+36 | | 12=6+2(x-14) | | (-8)*(6)*(-2)=x |